2011
DOI: 10.1055/s-0031-1296245
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and determination of acute and chronic pain activities of 1-[1-(3-methylphenyl) (tetralyl)]piperidine as a new derivative of phencyclidine via tail immersion and formalin tests

Abstract: Phencyclidine (1-(1-phenylcyclohexyl)piperidine, CAS 956-90-1, PCP, 1) and ketamine (2-O-chlorophenyl-2-methylaminocyclohexan, CAS 1867-66-9, II) revealed some analgesic effects. Some of their derivatives have been synthesized for biological properties studies. Utilizing 1-tetralone as a starting material, 1-[1-(3-methylphenyl)(tetralyl)]piperidine, (PCP-CH3-tetralyl, III) was synthesized and its analgesic effects were studied on rats via tail immersion (as a model of acute thermal pain) and formalin (as a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Thisw ill beunderstood ass uccessfuland satisfactory treatmentof pain. Suchtreatments arep resented in avast numberof scientificworksw hichh ave recentlyappeared in the field of applied analgesicor fundamentalresearchintonociception [1].Forexample, phencyclidine (1-(1-phenylcyclohexyl)piperidine,C AS 956-90-1,P CP, I ,S cheme 1) derivativesexhibiting analgesica ctivity arewell knownfort hispurpose [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thisw ill beunderstood ass uccessfuland satisfactory treatmentof pain. Suchtreatments arep resented in avast numberof scientificworksw hichh ave recentlyappeared in the field of applied analgesicor fundamentalresearchintonociception [1].Forexample, phencyclidine (1-(1-phenylcyclohexyl)piperidine,C AS 956-90-1,P CP, I ,S cheme 1) derivativesexhibiting analgesica ctivity arewell knownfort hispurpose [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…n Acuteand chronicpain n Analgesics n CAS 956-90-1 n Formalin test n Phencyclidine,derivative n Tail immersion test wasprepared and its analgesiceffects weree xamined on rats using tail immersion (asamodel of acutethermalpain) and formalin (asamodel of acuteand chronic chemicalpain) tests.The results arecompared withPCP and control groups.Asindicated in our previous work on thisfamily [4,6,8,9], incorporation of amethyl grouponthe aromaticring of the molecule will generate pronounced effects on electron distribution and dipole moments becauseo fi ts high electron donating character [14].Inaddition,incorporation of ahydroxylg roup on the piperidine ring of the molecule wasanticipated tohavepronounced effects on its hydrophilicproperties [3,15]and increasesthe polarity and solubility activities of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Inthe presents tudy,twon ewpyrrole derivativesof PCP withchangesin substitution on PCP'sphenyl groupand replacing the piperidine witharomaticpyrrole ringsweresynthesized. Asindicated in our previous worko nsubstitution of the methylgroup(high electron donating groupwithm oree lectron distribution and dipole moment), methylphenyl( tolyl) insteado fp henylgroupgeneratesstrongeranalgesiceffects [7,8].Inaddition because of the existenceo fp harmacological propertiesof pyrrole derivatives [10,11]and investigation on substituting aromaticpyrrole insteado fn onaromaticpiperidine group,suchn ewly developed changesw ereselected in our work. The results indicated that substitution of pyrrole insteado fp iperidine decreased the analgesiceffects of thisnewdrug( II)d ueto sharing of the non-bonding nitrogen electronsof pyrrole in the aromatic ring aswell asdecreasing the hydrophilicpropertiesof thisatom and drug( II).…”
Section: Discussionmentioning
confidence: 99%
“…Ithasbeen observed from our previous work [5][6][7][8] thatsubstituting amethylgroup(withhigh electron distribution and dipole moments [9])o nthe phenylring cani mpart higheranalgesiceffects in the synthesized drugs.Thereforethisgroupwasalsoadded too ur new and initiallys ynthesized drug( I )top roduceasecond compound ( III).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation